Supplementary file 1_Is Confucianism compatible with autonomous learning? An investigation of cultural influences on self-regulated learning in China.docx - Andrew Schenck (22682558) (2025)
Introduction Cultural values may impact how well a learner uses self-regulated learning strategies in Confucian contexts, yet research remains limited. Methods To address the gap in past research, surveys were given to 281 Chinese university students concerning preferences for Confucian values, self-regulated learning, and self-regulated use of technology. Confucian values were then statistically compared to preferences for self-regulated learning and use of technology using regression and Pearson correlations. Results Results suggest that traditional cultural values that promote collectivism and power distance significantly impact perspectives on self-regulated learning. However, these same cultural values do not appear to significantly influence perspectives on self-regulated use of technology. Whereas conceptions about learning have been clearly defined by long-standing Confucian traditions, perspectives on new educational technology have not, explaining the findings. Conclusion New techniques may be developed to enhance self-regulated learning in Confucian heritage countries. Educational techniques that mirror collective cultural beliefs and respect norms for power distance may enhance performance in the classroom.